Efficacy and safety of radiofrequency thermocoagulation target therapy for lumbar disc herniation: a systematic review - Cui, TianTian; Chen, WeiJie; Lui, ChunXiang; An, JiaLi; Zheng, WenKe (Frontiers in Surgery, 2025)
ObjectiveTo systematically evaluate the efficacy and safety of radiofrequency thermocoagulation target in the treatment of lumbar disc herniation.MethodsClinical randomized controlled trials (RCTs) on RFTT for LDH were collected by searching databases including CNKI (China National Knowledge Infrastructure), Wanfang Data, VIP Database, PubMed, Cochrane Library, and Web of Science. The search period spanned from the establishment of each database to December 8, 2023. Two reviewers independently screened the literature and extracted data in accordance with the inclusion and exclusion criteria. The risk of bias of the included studies was assessed using the Cochrane Handbook 5.3.0 risk of bias assessment tool. Review Manager 5.4 software was used to analyze outcomes including total effective rate, Visual Analog Scale (VAS) score, Japanese Orthopaedic Association (JOA) score, Oswestry Disability Index (ODI), and safety indicators.ResultsA total of 89 relevant studies involving 10, 079 participants were included, with 5,046 in the experimental group and 5,033 in the control group. The final analysis reviewed 89 studies, covering 10,079 participants. Among them, 5,046 participants were assigned to the experimental group and received the specific intervention, while the remaining 5,033 participants were in the control group and received conventional treatment. The analysis results showed that the total effective rate, JOA score, and ODI of the experimental group were significantly higher than those of the control group, indicating that the therapeutic effect of the experimental group was more pronounced than that of the control group. The incidence of adverse reactions was relatively consistent between the two groups, and most adverse reactions could be resolved through self-resolution without the need for intervention.ConclusionIn the treatment of LDH, radiofrequency thermocoagulation targeted surgery combined with conventional treatment is more effective than conventional treatment alone. It can better improve patients' quality of daily life and work ability, and this therapeutic approach significantly enhances patients' daily living quality and work capacity. However, due to the small sample size of the included studies and the low quality of relevant literature, the results of this study still require verification by more large-sample, multi-center, and high-quality clinical randomized controlled trials.